Spiritual Intelligence and Body Image Among Female Employees at Sulaymaniyah University (Raparin Journal of Humanities (RJH), 2025)
This study aimed to investigate the relationship between spiritual intelligence and body image among female employees of the University of Sulaymaniyah; and to determine whether there were statistically significant differences between the level of spiritual intelligence and the level of satisfaction with body image according to the variable of marital status (married, single), and age groups. This study was carried out. With a sample of (180) female employees, whose ages ranged between (25-55) years, they were chosen randomly. The results of the study indicate that the female employees of the study sample enjoy an average level of spiritual intelligence, and a high percentage of female employees in the study sample have a high level of their body image amounting to (82.22%), results also indicated that there is no difference due to the variables: marital status and age groups, and There was a positive correlation with statistical significance between the degrees of spiritual intelligence and the degrees of body image.